Implementasi Peraturan Gubernur Provinsi Jawa Tengah Nomor 53 Tahun 2019 dalam Pengembangan Desa Wisata Tuksongo, Kabupaten Magelang - Sigid Widyantoro; Akhni, Ghaziah Nurika; RM Mahendradi; Fadlurrahman (Universitas Widya Mataram, 2024)
Regulation of the Governor of Central Java Province Number 53 of 2019 is one of the prerequisites in developing tourism villages in regencies/cities in the Central Java region. Implementation of these regulations is carried out by creating a classification of Tourism Villages periodically every 4 years to determine the range of values used as a reference, including determination, management, development, guidance, and supervision of the tourism village; provide guarantees of legal certainty in the management of tourism villages; and basic determination of government financial assistance for the management and development of tourism villages. This paper analyzes the implementation of regulation and its challenges by focusing on Tuksongo village. This research uses a descriptive-qualitative research methodology. Findings show that based on the self-assessment on tourism village development, Tuksongo Village belongs to second category (developing) on the classification, which can be developed further to third category (developed) through improving several indicators: tourist attraction, accessibility, preservation and conservation of the environment, urban space planning, and village networking. Keywords: Tourism Village; Policy; Empowerment; Tourism Institutions.